2014
DOI: 10.1002/ijc.28825
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mammographic density over time in breast cancer cases and women at high risk for breast cancer

Abstract: High mammographic breast density is one of the strongest intermediate markers of breast cancer risk, and decreases in density over time have been associated with decreases in breast cancer risk. Using repeated measures of mammographic density in a cohort of high-risk women, the Women at Risk (WAR) cohort at Columbia University Medical Center (N=2670), we examined whether changes in pre-diagnostic mammographic density differed among 85 prospectively-ascertained breast cancer cases and 85 age-matched controls, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 23 publications
4
44
0
Order By: Relevance
“…A linear subject-specific trajectory of the latent variable is included in a relative risks survival model together with two of the most known breast cancer risk factors, family history of breast cancer and previous breast procedures. Our joint model for breast cancer and breast density is a good starting point that provides results consistent with the literature [16,18,19,21]. They are the basis for a rationale for extending the model and assessing its adequacy and accuracy.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A linear subject-specific trajectory of the latent variable is included in a relative risks survival model together with two of the most known breast cancer risk factors, family history of breast cancer and previous breast procedures. Our joint model for breast cancer and breast density is a good starting point that provides results consistent with the literature [16,18,19,21]. They are the basis for a rationale for extending the model and assessing its adequacy and accuracy.…”
Section: Discussionsupporting
confidence: 66%
“…Several studies have shown that high breast density is associated with increased breast cancer risk [7,[11][12][13][14], with risk estimates in the range four-fold to six-fold for women with very high breast density compared with women with low breast density [11,12]. Other studies have examined whether changes in breast density over time are associated to changes in breast cancer risk [15][16][17][18][19][20][21] and have suggested that monitoring changes in breast density could help to identify women at greater risk of disease. In most of the cases, the statistical methods used did not account for relevant characteristics of prospective studies like non-ignorable dropout mechanisms or internal time-dependent covariates [22].…”
Section: Introductionmentioning
confidence: 99%
“…There is mounting evidence that women with sustained levels of high breast density are at highest risk of breast cancer, those with low levels of breast density over time are at lowest risk and those that change density over time can increase or decrease their risk (9, 31). The IBIS-I has reported for women on tamoxifen that had a reduction in breast density of 10% or more, the risk of breast cancer was significantly reduced 52% relative to controls (10).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it may be important to assess the effect of antidiabetes agents and changes in glucose homeostasis on BD. Finally and encouragingly, change in BD over time is consistent with change in BC risk, 107,108 and reduced BD is associated with a reduced risk of BC 108,109 and death from the disease. 110 Therefore, BD may have potential utility as a biomarker for the efficacy of chemopreventive interventions.…”
Section: Discussionmentioning
confidence: 71%